2014
DOI: 10.1159/000365655
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Nail Lichen Planus with Alitretinoin: Report of 2 Cases and Review of the Literature

Abstract: Background: Treatment of nail lichen planus (LP) is difficult and an optimal therapy is lacking. Objective: To report additional cases to the scant existing literature to learn more about therapeutic options for nail LP. Methods: A regimen of 30 mg alitretinoin daily in 2 cases of nail LP over a period of 9 and 8 months, respectively. Results: In either case, nail changes showed marked improvement under oral alitretinoin therapy within 2 and 4 months, respectively. In both patients, affected nails with end-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…Appropriate interventions for the treatment of FFA are unclear owing to the paucity of high-quality therapeutic data. Based on several favorable reports of LP improvement following alitretinoin therapy (Alsenaid, Eder, Ruzicka, Braun-Falco, & Wolf, 2014;Brehmer, Haenssle, Schön, & Emmert, 2011), we effectively used oral alitretinoin to manage a patient diagnosed with FFA accompanied by LP.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate interventions for the treatment of FFA are unclear owing to the paucity of high-quality therapeutic data. Based on several favorable reports of LP improvement following alitretinoin therapy (Alsenaid, Eder, Ruzicka, Braun-Falco, & Wolf, 2014;Brehmer, Haenssle, Schön, & Emmert, 2011), we effectively used oral alitretinoin to manage a patient diagnosed with FFA accompanied by LP.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of alitretinoin are mediated by retinoic acid receptors (RAR) and/or retinoid X receptors (RXR) . As it has strong anti‐inflammatory effects and retinoid receptors are expressed in the matrix, nail disorders such as lichen planus, acrodermatitis continua of Hallopeau and keratitis–ichthyosis–deafness syndrome with nail dystrophy were reportedly responsive to alitretinoin . Moreover, Milanesi et al .…”
Section: Discussionmentioning
confidence: 99%
“…16 As it has strong anti-inflammatory effects and retinoid receptors are expressed in the matrix, nail disorders such as lichen planus, acrodermatitis continua of Hallopeau and keratitis-ichthyosis-deafness syndrome with nail dystrophy were reportedly responsive to alitretinoin. 4,[17][18][19][20] Moreover, Milanesi et al 21 described three patients with hand eczema accompanied by nail dystrophy who showed complete clearing of the nail lesions with alitretinoin. These reports support the use of alitretinoin as a therapeutic option in retinoid-responsive dermatoses with nail involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Localized LP lesions of the skin can usually be managed with standard topical therapy but certain subtypes or localizations may inherit a particular therapeutic resistance, which requires an individualized treatment (4)(5)(6)(7). LP localized to lower limb (LPLL) manifests a great challenge because of severe life impacting itching and the resistance to standard topical therapies (2).…”
Section: Discussionmentioning
confidence: 99%